2019
DOI: 10.1016/j.jaci.2018.12.905
|View full text |Cite
|
Sign up to set email alerts
|

Association study in African-admixed populations across the Americas recapitulates asthma risk loci in non-African populations

Abstract: RATIONALE: Pulmonary mast cells (MC) have been associated with asthma pathogenesis. We have previously shown differences in MC phenotype by location in the lung (submucosa and epithelium) [Balzar, AJRCCM, 2011]. Little is known regarding the relative importance of luminal MCs to asthma. We hypothesized that distal/luminal MCs would better predict more severe clinical outcomes than proximal/epithelial MCs. METHODS: In 102 University of Pittsburgh asthmatics enrolled in NHLBI trials, bronchial epithelial brushi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 0 publications
0
49
0
1
Order By: Relevance
“…Of these regions, 41 loci were not previously known to be associated with asthma or the combined phenotype of asthma and allergic diseases. The remaining 104 overlapped with the 146 loci previously identified for either asthma alone in adults, children, or subjects from multiple ancestries, or the combined phenotype of asthma, eczema, and hay fever [5][6][7][8][9][10][11][12][13] (Supplementary Data 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these regions, 41 loci were not previously known to be associated with asthma or the combined phenotype of asthma and allergic diseases. The remaining 104 overlapped with the 146 loci previously identified for either asthma alone in adults, children, or subjects from multiple ancestries, or the combined phenotype of asthma, eczema, and hay fever [5][6][7][8][9][10][11][12][13] (Supplementary Data 2).…”
Section: Resultsmentioning
confidence: 99%
“…Second, recent studies have shown that both common and distinct loci underlie susceptibility to asthma in adulthood and in children 10,11 , but we did not take age of onset into account for our analyses in order to increase power for detecting associations and due to the unavailability of this information in publicly available summary data from the TAGC. Third, since most subjects in the UK Biobank and TAGC were of European ancestry, some, but not all, of the genetic associations we identified may be relevant in non-European populations 9 . This notion has previously been observed with both common and rare variants even among closely related Latino populations and in comparison, to subjects of African ancestry 14,58 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In this study, the investigators found rs28450894 (located within NFKB1 and quantitative trait locus for SLC39A8 ), which is significantly associated with drug response, was predominantly found in African ancestry populations (8.8–28.7%), vs. European populations (3.7–7.6%) and Puerto Ricans (6.2%), and Mexicans (1.5%) . An admixture mapping meta‐analysis of genetic ancestry identified a new locus at 18q21 that contributed to asthma susceptibility and therapies in Latinos and a recent paper identified two novel loci in 8p23 and 8q24 specific to asthma risk in African populations . These novel loci found through admixture mapping and population‐specific cohorts may yield novel drug targets and biomarkers that may be useful, if replicated, for patient stratification.…”
Section: Pharmacogenomics and Minority Populationsmentioning
confidence: 77%
“…80 An admixture mapping meta-analysis of genetic ancestry identified a new locus at 18q21 that contributed to asthma susceptibility and therapies in Latinos 84 and a recent paper identified two novel loci in 8p23 and 8q24 specific to asthma risk in African populations. 85 These novel loci found through admixture mapping and population-specific cohorts may yield novel drug targets and biomarkers that may be useful, if replicated, for patient stratification.…”
Section: Asthma Pharmacogenomics In Diverse Populationsmentioning
confidence: 99%